Prognóstico da anemia em pacientes com insuficiência cardíaca crônica sistólica secundária à cardiomiopatia chagásica - Miguel, Carlos Eduardo (2012)
Introduction: The purpose of this study was to evaluate the prognostic significance of anemia on outcome of patients with chronic systolic heart failure secondary to Chagas cardiomyopathy, as no previous study has addressed this question. Patients and Methods: One-hundred-eight-six patients prospectively followed for chronic systolic heart failure secondary to Chagas cardiomyopathy at Hospital de Base de São José do Rio Preto, from January, 2000 to April, 2008 were studied. Forty-nine (26%) patients were found to have anemia; 37 (20%) were men and 12 (6%) were women. Mean hemoglobin level was 14,1 ± 1,2 g/L in patients with no anemia and 11,5 ± 1,2 g/L in patients with anemia. Results: On a Cox proportional hazards multivariate analysis, anemia was a predictor of all-cause mortality neither in the univariate nor in the multivariate analysis. Mean serum sodium (Hazard ratio = 0.92; Beta-coefficient = -0.09; 95% confidence interval 0.89-0.96; p value < 0.005), and Beta-Blocker therapy (Hazard ratio = 0.40; 95% confidence interval 0.26-0.61; p value <0.005) were retained as independent predictors of mortality for patients with Chagas cardiomyopathy with chronic heart failure. Probability of survival for patients with anemia, however, was significantly lower in patients with anemia in comparison to patients with no anemia, mainly in patients with advanced heart failure. Conclusion: Anemia is not an independent predictor of all-cause mortality in patients with Chagas cardiomyopathy with chronic systolic heart failure. Probability of survival is poorer in patients with anemia than in those without.